The effect of varicocoelectomy on the relationship of oxidative stress in peripheral and internal spermatic vein with semen parameters. (5th March 2016) - Altintas, R.; Ediz, C.; Celik, H.; Camtosun, A.; Tasdemir, C.; Tanbek, K.; Tekin, S.; Colak, C.; Alan, C.
Summary: The aim of this prospective controlled study was to investigate the levels of reactive oxygen species (ROS), including asymmetric dimethylarginine (ADMA), oxidative stress index (OSI) and total oxidant capacity (TOC), and antioxidants with total antioxidant capacity (TAC) in peripheral and internal spermatic veins blood, the relationship of these factors with sperm parameters in the infertile varicocoele patients, and the amelioration effect of varicocoelectomy on these outcomes. Thirty‐one primary infertile varicocoele patients and 31 fertile control patients evaluated for determining the levels of ADMA, TOC, OSI, superoxide dismutase (SOD), glutathione (GSH), TAC, and semen analysis. The patients' preoperative SOD, GSH and TAC levels, which were significantly lower than the controls, significantly increased postoperatively. Although SOD and GSH were significantly higher in spermatic vein compared to median cubital vein, TAC was significantly higher in median cubital vein. ADMA, TOC and OSI were significantly higher in the patient group. TOC and OSI were significantly higher in spermatic vein compared to median cubital vein. Postoperative TOC, OSI and ADMA reduced to the control levels. Total antioxidant capacity in the peripheral circulation and oxidative stress index in the internal spermatic vein could give an idea about the possible improvement in sperm count acquired by varicocoelectomy.